2019
DOI: 10.3389/fvets.2019.00007
|View full text |Cite|
|
Sign up to set email alerts
|

Decrease in Population and Increase in Welfare of Community Cats in a Twenty-Three Year Trap-Neuter-Return Program in Key Largo, FL: The ORCAT Program

Abstract: The objective of this study was to evaluate the effect of a long-term (23-year) trap-neuter-return program on the population size of community cats in the Ocean Reef Community and to describe the demographic composition and outcome of enrolled cats. A retrospective study was performed using both cat census data collected between 1999 and 2013 as well as individual medical records for cats whose first visit occurred between 3/31/1995 and 12/31/2017. Medical record entries were reviewed to determine program inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 23 publications
6
65
0
3
Order By: Relevance
“…All articles focusing on free-roaming cats included a form of trap-neuter-return, as either the only method or one of the methods of cat population management, and, therefore, TNR appears to be the most widely accepted, or at least the most widely reported, non-lethal cat population management practice, though it is variable in delivery. Collectively, these TNR studies report varying degrees of success in controlling cat populations, with little to no effect on free-roaming cat populations reported in the short-term TNR programs in urban NYC [21] or rural Quebec [23], whereas the longer term (9-20 years) studies (n = 4) demonstrated significant decreases in free-roaming cat populations in rural and urban areas of the USA and Australia of between 54% and 100% [25][26][27][28]. However, all four long-term TNR programs were supplemented with removal (TR); mainly adoption/rehoming of social cats and the euthanasia of cats that tested positive to FeLV or FIV (feline leukemia and feline immunodeficiency virus respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All articles focusing on free-roaming cats included a form of trap-neuter-return, as either the only method or one of the methods of cat population management, and, therefore, TNR appears to be the most widely accepted, or at least the most widely reported, non-lethal cat population management practice, though it is variable in delivery. Collectively, these TNR studies report varying degrees of success in controlling cat populations, with little to no effect on free-roaming cat populations reported in the short-term TNR programs in urban NYC [21] or rural Quebec [23], whereas the longer term (9-20 years) studies (n = 4) demonstrated significant decreases in free-roaming cat populations in rural and urban areas of the USA and Australia of between 54% and 100% [25][26][27][28]. However, all four long-term TNR programs were supplemented with removal (TR); mainly adoption/rehoming of social cats and the euthanasia of cats that tested positive to FeLV or FIV (feline leukemia and feline immunodeficiency virus respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Four articles assessed the impact of long-term conventional TNR programs on free-roaming cat populations in the United States [25][26][27], and in Australia [28], over extended periods of time; 23, 15, 10 and 9 years respectively. A US study [25] retrospectively evaluated a 23-year TNR program through census data collected before and during the program (program is ongoing).…”
Section: Long-term Tnr Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of cats owned in Japan has kept increasing and was estimated at 9,649,000 in 2017, exceeding that of dogs (8,903,000) for the first time [5]. Despite this fact, cats have been euthanized in public animal shelters much more than dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Free‐roaming cat management and monitoring programs are often conducted by local authorities, government officers, and animal rights organizations, and not by professional ecologists (Galvis et al, , Gunther et al, ; Hughes, Slater, & Haller, , Kreisler, Cornell, & Levy, , Natoli et al, , Zito, Aguilar, Vigeant, & Dale, ). Consequently, within this reality, there is a necessity to develop a monitoring scheme that is both reliable and valid on the one hand, and simple and applicable on the other hand.…”
Section: Introductionmentioning
confidence: 99%